Playing and Entertainment Design for children with disabilities (7-11 years old) - Atefeh Vahdati Eadgahi; Khan Shirazi Masoud; Noori Mehrdad (Association of Social and Educational Innovation, 2017)
The present research is a descriptive study, which initially began by providing the definitions of the vocabulary and its types and games and its effects on the child. They have addressed the moral abnormalities of children with disabilities (aggression, withdrawal, and lack of self-confidence), with regard to the theories on the effects of the game on the social skills of children, then the interests of children in different age groups are examined and successful domestic and foreign examples of toys produced for the disabled are considered. And with regard to your respectful opinion, and an interview with the expert on the subject, Playboard approaches are provided. In the games presented, the theme intended by the designer is how to connect the child to the game and how to train the type of the game. In the three games presented, the emotional relationship between the child and the toy has been considered as well as creative, motivational, and collaborative learning.